Late surgical correction of hypospadias increases the risk of complications: a series of 501 consecutive patients. (1st February 2017) - Garnier, Sarah; Maillet, Olivier; Cereda, Barbara; Ollivier, Margot; Jeandel, Clement; Broussous, Sylvie; Lopez, Christophe; Paris, Francoise; Philibert, Pascal; Amouroux, Cyril; Jeandel, Claire; Coffy, Amandine; et al.
Abstract : Objectives: To evaluate the outcomes of hypospadias surgery according to age and to determine if some complications are age‐related. Patients and Methods: This retrospective study was based on 722 boys with hypospadias undergoing primary repair. A total of 501 boys underwent urethroplasty and were included in the study. Complications requiring an additional procedure (stenosis, fistula, dehiscence, relapse of curvature, urethrocele) were included in the analysis, as well as healing problems, infections, haematomas and detrusor‐sphincter dyssynergy. Logistic regression analysis was performed. Results: Hypospadias was anterior in 63.1%, mid‐penile in 20.5%, posterior in 8.4% and scrotal in 7.9% of the boys. The median (range) age was 4 (1–16) years. The overall rates of re‐intervention and complications were 22.8% and 36.2%, respectively. Age >2 years was a significant predictor of complications ( P = 0.002, odds ratio 1.98 [95% confidence interval 1.26–3.13]). Some periods of time appeared to be associated with a specific complication: dyssynergy was more common between the ages of 24 and 36 months (12.5 vs 3.6%; P = 0.01) and healing problems were more common in boys aged >13 years (1.5 vs 28.5%; P = 0.06). Conclusion: Delayed surgery may be detrimental for patients. Factors related to age may influence the rate of complications. After the age of 2 years, urethral surgery may interfere with the normal toilet‐training process. During puberty, endogenous testosterone may alter healing. Even if no specific data exist for severe hypospadias, it may be prudent to continue to advocate early surgery in patients with disorders of sex development.